Third Place Award: Posttraumatic elbow arthrofibrosis incidence and risk factors. Issue 4 (July 2017) - Marchand, Lucas S.; Working, Zachary M.; Williams, John B.; Elliott, Iain S.; Higgins, Thomas F.; Rothberg, David L.; Kubiak, Erik N.
Abstract : Background: Loss of elbow range of motion (ROM) can significantly decrease patient quality of life. Posttraumatic arthrofibrosis is a common cause of decreased elbow ROM, and it has been reported that loss of 50% of elbow motion can compromise 80% of extremity function. The aim of this study was to examine the incidence and risk factors of posttraumatic elbow arthrofibrosis. Methods: We performed a retrospective review of all patients with intraarticular elbow fracture treated with operative fixation over a 10-year period. Pearson's Chi-squared, Student's t-test, and a logistic multivariate regression model was used to predict arthrofibrosis risk factors. Results: A total of 390 consecutive patients with intra-articular elbow fractures were identified. A total of 105 (27%) patients developed arthrofibrosis with 72 surgical interventions performed to improve ROM. At final follow-up 88 (23%) patients had persistent arthrofibrosis. Using multivariate regression analysis, high-energy mechanism (odds ratio (OR) 3.61, 95% confidence interval (CI) 1.16-6.3, P <0.001), deep post operative infection (OR 2.3, 95% CI 1.26-4.37, P =0.038), elbow fracture-dislocations (OR 3.44, 95% CI 1.32-7.41, P =0.005), and distal humeral fractures (OR 1.9, 95% CI 1.1-3.19, P =0.027) were significantly associated with the development of arthrofibrosis. The effect of duration of immobilization was significant, with each extra day of immobilization increasing the odds of arthrofibrosis by 9% (OR 1.09, P =0.001). Conclusions: Duration of immobilization, fracture pattern, presence of deep postoperative infection, and energy of injury were all predictive factors for the development of elbow arthrofibrosis after operative treatment of intraarticular elbow fractures.